History of Syria from ancient times to the Ottoman period / Yusuf al-Dibs. - 880-01 Dibs, Yûsuf b. İlyâs, 1833-1907. (Piscataway, NJ)
8 cilt
Keywords: “This monumental eight-volume history of Syria in Arabic was a labor of love by Archbishop Yusuf al-Dibs. A native of Syria, he undertook to cover as much of the history of his native land as possible. The first volume covers the ancient peoples of Syria, including the Hittites and Phoenicians. The Hebraic peoples are studied in volume 2. The next volume traces the history of the country from the conquest of Alexander the Great through the Roman occupation in the second century. Volume 4 continues the Roman occupation and takes the reader through the Islamic conquest into the First Caliphate. The Umayyad and Abbasid Caliphates to the end of the eleventh century occupy volume 5. Volume 6 covers the Crusades, Maronite-Papal relations, and the biographies of important figures in Syria up to the fifteenth century. The final two volumes are concerned with the Ottoman Empire. One of the essential features of al-Dibs’ study is the attention that he gives to Eastern Christianity throughout the historical period. Biographies of figures in Syrian history from the fifteenth century are rare, making al-Dibs one of the major historical sources for this information. A major resource, difficult to locate in the western world, al-Dibs history of Syria is essential for any Arabist interested in this region“ -- Yayıncı.